Anatomical evaluation of supraorbital notch and supraorbital foramen morphology and supraorbital nerve distribution: a cadaveric study - Yildiz, Nilay; Chatzioglou, Gkionoul Nteli; Gayretli, Ozcan (International Journal of Research in Medical Sciences, 2025)
Background: Peripheral nerve compression at trigger points is considered a cause of migraine and primary headaches. These trigger points are most commonly found in the sensory regions. In particular, compression of the supraorbital nerve by fascial bands or at the supraorbital foramen has been reported as a source of headache in the literature. This study aimed to evaluate the structures through which the supraorbital nerve passes to reach the innervation area. Methods: Eleven female and 11 male cadaver heads fixed with formalin were dissected and the formation of the supraorbital nerve emerging the cranium was evaluated. Results: Cadaveric sides were divided into four types based on the presence of a notch or foramen. Sides with only one notch constituted the majority at 45.4% (Type A). Conclusions: In this study, in cases with only supraorbital notch, the distance of the notch to the midsagittal line was found to be 23.51±3.74 mm on the right side and 22.77±3.75 mm on the left side on average. In cases with only supraorbital foramen, the right side average was calculated as 20.50±4.30 mm and the left side average was calculated as 25.60±3.83 mm. These measurements are of considerable importance in procedures such as migraine botox or migraine surgery.